Permanganate-Oxalic acid Reaction: Autocatalytic Suppression in Surfactant Media - Venkataraman, R.; Raghavan, P.S. (Asian Journal of Chemistry, 2010)
The pennanganate-oxalic acid reaction is a well known autocatalytic redox reaction, due to the catalytic effect of the Mn2+ ion formed during the course of the reaction. In the present paper, it has been shown that this autocatalysis can be suppressed in micellar media.